1985
DOI: 10.1159/000183476
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Glomerulonephritis and Exposure to Organic Solvents

Abstract: Exposure to organic solvents was compared by interview and questionnaire in 50 patients with biopsy-proven proliferative glomerulonephritis in whom there was no evidence of systemic disease or preceding infection with that of 100 control subjects matched for age, sex and social class. The interview was conducted by a lay person who did not know whether the interviewee was a patient with glomerulonephritis or a control subject. The exposure scores derived from the results of the questionnaires were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 4 publications
2
24
0
Order By: Relevance
“…There was a significantly higher number of exposed individuals in the GN group than in the control group [116]. These findings were consistent with a previous study by Bell et al [117], who recorded a dose-response relationship between exposure to hydrocarbons and GN. A collaborative animal experimental study also demonstrated a wide range of lesions in the nephrons of animals exposed to hydrocarbons compared to the controls.…”
Section: Nephrotoxicitysupporting
confidence: 91%
“…There was a significantly higher number of exposed individuals in the GN group than in the control group [116]. These findings were consistent with a previous study by Bell et al [117], who recorded a dose-response relationship between exposure to hydrocarbons and GN. A collaborative animal experimental study also demonstrated a wide range of lesions in the nephrons of animals exposed to hydrocarbons compared to the controls.…”
Section: Nephrotoxicitysupporting
confidence: 91%
“…The first reported cases were rapidly progressive GN with or without anti-glomerular basement membrane antibodies, a severe but rare type of GN (3). A few cases of membranous nephropathy (MN) (4), IgA nephropathy (IgAN) (5), and FSGS (6) were described later in solvent-exposed workers, but concern definitely rose from a number of case-control studies that included chronic GN as well as other types of chronic kidney disease (CKD) (2,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Although some of these studies were criticized for their methodologic weaknesses with respect to sample size and inaccuracy in case definition or exposure assessment, most of them showed significant associations of solvent exposure with various types of primary or secondary chronic GN (2,7,8,10 -12,14 -19), except for three, which were negative (9,13,21).…”
mentioning
confidence: 99%
“…In contrast, several of the previous studies of organic solvents and renal disease were hospital based (2,3,6,9,10,12,25) or had control selection procedures that did not guard against influence of solvent exposure status or could not ensure that cases and control subjects represented the same study base (26). Moreover, as opposed to most previous studies, which concerned patients with ESRD (2,4,8,10), we defined incident cases as those who permanently passed a predefined serum creatinine level-a level sufficiently high to avoid the possible bias linked to detection of clinically silent disease (comorbidity or other circumstances leading to a higher probability for serum creatinine testing) yet sufficiently low to ensure that most case patients had not reached ESRD.…”
Section: Discussionmentioning
confidence: 97%
“…In the very first investigation published, the exposure scores used were poorly defined (2). The exposure score developed by Ravnskov et al (3) and later used in several studies (6,9,10,15,23,25) represents an improvement, but the assessment scale with exposure intensity factors according to 17 predefined occupational activities was crude and may have led to varying degrees of misclassification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation